Doctors taking bribes from pharmaceutical companies is common and not substantially reduced by an educational intervention: a pragmatic randomised controlled trial in Pakistan - Afifah Rahman-Shepherd; Johanna Hanefeld; Mishal Khan; Charles Opondo; Sameen Siddiqi; Virginia Wiseman; Iqbal Azam; Wafa Aftab; Sadia Shakoor; Amna Rehana Siddiqui; Rumina Hasan; Zafar Mirza; et al. (BMJ Global Health)
Introduction Incentive-linked prescribing, which is when healthcare providers accept incentives from pharmaceutical companies for prescribing promoted medicines, is a form of bribery that harms patients and health systems globally. We developed a novel method using data collectors posing as pharmaceutical company sales representatives to evaluate private doctors’ engagement in incentive-linked prescribing and the impact of a multifaceted educational intervention on reducing this practice in Karachi, Pakistan.Methods We made a sampling frame of all doctors running for-profit, primary-care clinics and randomly allocated participants to control and intervention groups (1:1). The intervention group received a multifaceted seminar on ethical prescribing and reinforcement messages over 6 weeks. The control group attended a seminar without mention of ethical prescribing. The primary outcome was the proportion of participants agreeing to accept incentives in exchange for prescribing promoted medicines from data collectors posing as pharmaceutical company representatives, 3 months after the seminars.Results We enrolled 419 of 440 eligible participants. Of 210 participants randomly allocated to the intervention group, 135 (64%) attended the intervention seminar and of 209 participants allocated to the control group, 132 (63%) attended the placebo seminar. The primary outcome was assessed in 130 (96%) and 124 (94%) of intervention and control participants, respectively. No participants detected the covert data collectors. 52 control group doctors (41.9%) agreed to accept incentives as compared with 42 intervention group doctors (32.3%). After adjusting for doctors’ age, sex and clinic district, there was no evidence of the intervention’s impact on the primary outcome (OR 0.70 [95% CI 0.40 to 1.20], p=0.192).Conclusions This first study to covertly assess deal-making between doctors and pharmaceutical company representatives demonstrated that the practice is strikingly widespread in the study setting and suggested that substantial reductions are unlikely to be achieved by educational interventions alone. Our novel method provides an opportunity to generate evidence on deal-making between doctors and pharmaceutical companies elsewhere.